P- and S-wave delays caused by thermal plumes - Maguire,R; Ritsema,J; van,Keken PE; Fichtner,A; Goes,S (Geophysical Journal International, 2016)
Many studies have sought to seismically image plumes rising from the deep mantle in order to settle the debate about their presence and role in mantle dynamics, yet the predicted seismic signature of realistic plumes remains poorly understood. By combining numerical simulations of flow, mineral-physics constraints on the relationships between thermal anomalies and wave speeds, and spectral-element method based computations of seismograms, we estimate the delay times of teleseismic S and P waves caused by thermal plumes. Wave front healing is incomplete for seismic periods ranging from 10 s (relevant in traveltime tomography) to 40 s (relevant in waveform tomography). We estimate P-wave delays to be immeasurably small (<0.3 s). S-wave delays are larger than 0.4 s even for S waves crossing the conduits of the thinnest thermal plumes in our geodynamic models. At longer periods (>20 s), measurements of instantaneous phase misfit may be more useful in resolving narrow plume conduits. To detect S-wave delays of 0.4–0.8 s and the diagnostic frequency dependence imparted by plumes, it is key to minimize the influence of the heterogeneous crust and upper mantle. We argue that seismic imaging of plumes will advance significantly if data from wide-aperture ocean-bottom networks were available since, compared to continents, the oceanic crust and upper mantle are relatively simple.